Diagnosis Kecemasan Statistik Pendidikan Pada Mahasiswa Non-Matematika FTIK IAIN Langsa - Nazliati Nazliati; Rita Sari; Fitriani Fitriani (Center for Research and Community Service (LPPM) University of Abulyatama, 2019)
Educational Statistics is considered as one of the most difficult subjects, where most of students try to avoid or postpone to take it. This condition has increased the anxiety among non – mathematics’ students. SPSS is one of statistics software that assists students in analyzing data. This paper examined the non mathematics students’ anxiety after using SPSS and the SPSS’s contribution in reducing non mathematics students’ anxiety in studying statistics. The questioner and test are given to 25 non mathematics students, who are selected randomly from teacher training faculty. The finding revealed that SPSS is effective enough to help reducing the non mathematics students’ anxiety. The positive contribution of SPPS was showed on finding result, which are 23% for lower level of anxiety, 60% for the middle level of anxiety and 79% for panic level.